2020
DOI: 10.18332/tid/120188
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the ENSP eLearning platform on improving knowledge, attitudes and self-efficacy for treating tobacco dependence: An assessment across 15 European countries

Abstract: INTRODUCTION In 2018, the European Network for Smoking Cessation and Prevention (ENSP) released an update to its Tobacco Treatment Guidelines for healthcare professionals, which was the scientific base for the development of an accredited eLearning curriculum to train healthcare professionals, available in 14 languages. The aim of this study was to evaluate the effectiveness of ENSP eLearning curriculum in increasing healthcare professionals' knowledge, attitudes, self-efficacy (perceived behavioral control) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…As a result, use of evidence-based smoking cessation treatment and cessation aids in general is suboptimal in Europe [ 13 , 54 , 55 , 56 ]. Increased funding for smoking cessation services and aids especially for high risk populations (e.g., those with chronic diseases, severe mental illness, addiction HIV, Tuberculosis, as well as pregnant women) and building on the capacity of healthcare professionals to provide tobacco treatment services, (e.g., by offering hands-on training or digital training [ 57 , 58 ]) could improve the smoking cessation landscape in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, use of evidence-based smoking cessation treatment and cessation aids in general is suboptimal in Europe [ 13 , 54 , 55 , 56 ]. Increased funding for smoking cessation services and aids especially for high risk populations (e.g., those with chronic diseases, severe mental illness, addiction HIV, Tuberculosis, as well as pregnant women) and building on the capacity of healthcare professionals to provide tobacco treatment services, (e.g., by offering hands-on training or digital training [ 57 , 58 ]) could improve the smoking cessation landscape in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking has been linked to higher disease severity in COVID-19 and has also been associated with higher expression of ACE-2. Since smoking is more prevalent in men it can predispose men to a worse clinical prognosis [ 68 ]. Studies have also shown that women tend to use more healthcare services than men and employ better hygiene practices [ 69 ].…”
Section: Introductionmentioning
confidence: 99%
“…E-learning is an innovation that can be used in the learning process not only to provide learning materials, but also to improve students' learning abilities in various functions [6]. Through e-learning, students can not only read the description of the material, but also see its images and animations, listen to audio to see videos related to the learning material studied [7]. Using E-learning in the learning process can improve students' knowledge and skills.…”
Section: Introductionmentioning
confidence: 99%